The interdisciplinarity dilemma: Public versus private interests - Magda Fontana; Martina Iori; Valerio Leone Sciabolazza; Daniel Souza (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
In this paper, we investigate how the choice to conduct interdisciplinary work affects a researcher's career. Using data on 23,926 articles published by 6,105 researchers affiliated with the University of Florida in the period 2008-2013, we show that synthesizing knowledge from diverse fields pays off in terms of reputation. However, if combining too-distant research fields, the impact of a work is penalized. Moreover, research conducted balancing the contribution of different scientific fields has a negative impact on the reputation of scientists in terms of the number of citations but a positive impact on the diffusion of knowledge across other disciplines. Our findings are robust to a number of controls, including individual, time, and field of study fixed effects, and they apply to all investigators regardless of their gender, collaboration behavior, performance, and affiliation. All in all, despite its public benefits, interdisciplinary research comes with a cost for a researcher's academic career. This trade-off poses challenging questions to policymakers.
Keywords: I23; H5; O39; 330; Interdisciplinarity; Research Policy; Academic Career; Generality; Incentives; Citations